Spermiogram of wild and captive Malaysian horseshoe crab (Tachypleus gigas) from Pantai Balok, Kuantan, Pahang, Malaysia =Spermiogram belangkas liar dan kurungan Malaysia (Tachypleus gigas) dari Pantai Balok, Kuantan, Pahang, Malaysia) - Sheikh, Hassan I.; Yunus, Kamaruzzaman; John, Akbar; Kassim, Zaleha; Arief Ichwan, Solachuddin Jauhari (Penerbit UKM, 2019)
Horseshoe crab (HSC) populations around the world are declining in recent decades mainly due to destruction of breeding grounds and habitats. A short-term solution for this problem is captive breeding and artificial rearing. This experiment aimed at looking for a source of good sperm donors for in-vitro fertilization and captive breeding. Tachypleus gigas were collected from Balok Beach, Kuantan, Pahang, Malaysia. Crabs were divided to wild and captive groups. Wild T. gigas sperm was collected on the same day, while sperm of captive T. gigas was collected after 5 months of captivity to assess captivity effect on sperm traits. Sperm density and sperm viability were studied and correlated to morphometric measurements. The results indicated that T. gigas from Balok is a good sperm donor. Captivity was found to affect sperm traits where sperm density dropped significantly and sperm viability increased slightly. Intraocular width to carapace width ratio (IO-Car) of the HSC body correlated to sperm density, hence can be used as an indicator for donor selection during sampling. In conclusion, T. gigas from Balok can be used as a sperm donor for in-vitro fertilization for T. gigas propagation.